Spirituality and Social Work: Selected Canadian Readings - Moss, Bernard R. (Implicit religion, 2009)
The article reviews the book "Spirituality and Social Work: Selected Canadian Readings," by John Coates, John R. Graham, Barbara Swartzentruber, and Brian Ouelette.